Pengaruh Sumber Daya Teknologi Informasi dan Keselarasan Strategis terhadap Kinerja Organisasi: Peran Moderasi Ketidakpastian Lingkungan pada Transformasi Digital - Rachmiani; Oktadinna, Nabila Kintan; Fauzan, Tribowo Rachmat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Digital transformation encourages organizations to leverage information technology strategically to improve performance and operational efficiency. This study examines the impact of IT resources and strategic alignment on organizational performance, including the moderating role of environmental uncertainty. Data were collected from 90 respondents, comprising 45 IT managers and 45 executive managers from public and private sector organizations, using a 74-item questionnaire and analyzed with WarpPLS6. Results indicate that IT management and strategic alignment positively influence performance, while IT investment without effective management does not yield significant effects. Environmental uncertainty strengthens the influence of IT management and strategic alignment on performance, particularly when organizations adapt their strategies to external changes. The interaction between IT investment and management also improves performance, but its effect diminishes under high uncertainty if adaptive strategies are insufficient. These findings highlight the importance of integrating IT governance, business strategy, and adaptive responses to change in achieving superior outcomes. Balanced strategies encompassing technology investment, management, and alignment enable organizations to enhance productivity, innovation, and competitiveness sustainably.